Pengelolaan Media Sosial Instagram Humas Polda Jabar dalam Meningkatkan Citra Positif Institusi Polri - Ilham Faturrohman; Sri Wahyuning Astuti∗ (Universitas Telkom, 2024)
The hectic number of cases carried out by unscrupulous members of the Police has resulted in a decline in the image ofthe Police in society. The two most shocking cases involved high-ranking National Police officers who respectively carriedout shooting scenarios and selling drug evidence. The use of Instagram social media by the Public Relations Division of theWest Java Regional Police is one of the efforts to improve the image of the institution in the eyes of the public. The purposeof this research is to find out how the Public Relations Division of the West Java Regional Police contributes to and utilizesexisting features on Instagram to restore image and increase public trust. This study used a qualitative method involvingtwo informants from the West Java Regional Police Public Relations, one informant from lecturers who had disciplines inthe field of digital media, and three informants from followers of the West Java Regional Police Public Relations Instagramaccount who had been interviewed to get the results obtained. accurate and credible. The results of this study concludedthat the Public Relations Division of the West Java Regional Police had carried out a number of stages put forward by Cutlip,Center and Broom, but the image enhancement through social media was still not optimal because the uploads still seemedstiff and homogeneous.